The Lived Experiences of Indigenous Working Mothers in the Pursuit of Tertiary Education - Tohdoh, Maria Aizin R.; Regaspi, Rene B. (Future Science / FSH-PH Publications, 2025)
This paper describes the lived experiences of Indigenous working student mothers in pursuing tertiary education in Zambales. It focuses on describing and finding meaning in their lived challenges and discovering their day-to-day struggles and experiences. It aims to propose a guidance and counseling support program that would help them ease their difficulties. A descriptive phenomenological research approach was employed, with respondents purposively selected to ensure that individuals with rich, relevant experiences related to the phenomenon under investigation were included. Data were gathered through one-on-one in-depth interviews with 12 respondents following a set of inclusion criteria. The respondents represented the Indigenous group of working student mothers enrolled in tertiary education in Zambales. Results of the study revealed that respondents describe their lived experiences as a challenge to their well-being. They describe being a mother as the most challenging job among other roles. Other challenges they identified included balancing parenthood and personal growth, time management problems, financial struggles, and academic challenges. Despite the hurdles they were facing, they found significance in their adversity. They experienced a profound sense of empowerment in their role as a model for others, emphasizing personal achievement, strength, and motivation, and inspiring dignity. A proposed guidance and counseling support program was designed to help this special group of students overcome their difficulties while pursuing tertiary education. Conclusions and recommendations are also provided.